The Political Economy of Muslim Identity in 411 Action by Online Media (Semiotic Analysis of Tribunnews Journalists Reports on Youtube) - Syafuddin, Khairul (Islamic Studies Journal for Social Transformation, 2023)
The People's Defenders National Movement (GNPR) held the 411 Action to demand President Jokowi step down from his position. Even though the action was in the name of defending the people, it contained the practice of Muslim identity politics. This Muslim identity can be exploited by the media to reap benefits from the audience. The theory in this research is propaganda and commodification. The purpose of this study is to analyze Tribunnews' efforts to make a profit in the context of political economy. This study uses qualitative methods through semiotic analysis of Rolland Barthes. The results of this study see that Muslim identities tend to be displayed in Tribunnews live reports. Setting the point of view of the journalist's camera makes Muslim identity a spectacle material to be used as a commodity material. In addition, the selection of action images also strengthened the propaganda message of the demonstration. There are various signs displayed in the live report, such as white cloth clothes, caps, and other clothes that symbolize Islamic religious identity. In addition to commodification, there are propaganda practices carried out through this media. Propaganda practices are carried out to build a position between the protagonist and antagonist through broadcasts on Youtube.